Application of process system engineering tools to the fed-batch production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) from a vinasses–molasses Mixture (2019)
ABSTRACT : Fed-batch production of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) copolymer using vinasses–molasses mixture is carried out in this work by implementing different process systems engineering tools. Two fed-batch strategies are tested experimentally at 5 L scale, considering only offline information: (1) offline optimizing control and (2) exponential feeding. Application of these strategies showed that different feeding profiles result in different dynamic behaviour, influencing both, yield and biopolymer properties. As offline-based feeding strategies do not consider information of the culture status, they cannot deal with uncertainties. Therefore, a closed loop control strategy was implemented, which uses biomass and substrate information predicted online by soft-sensors. Results demonstrated the technical feasibility to produce biopolymer using a 75/25%vol. vinasses–molasses mixture. Successful implementation of the soft-sensor-based control strategy was evidenced at pilot plant scale, where sugar concentration was kept almost constant for 14 h, while obtaining the desired copolymer. Thus, proposed control strategy could be of interest at industrial-scale.